The Effectiveness of the Safety Planning Intervention for Adults Experiencing Suicide-Related Distress: A Systematic Review. Issue 3 (3rd July 2022) - Ferguson, Monika; Rhodes, Kate; Loughhead, Mark; McIntyre, Heather; Procter, Nicholas
Abstract: The safety planning intervention (SPI) is gaining momentum in suicide prevention practice and research. This systematic review sought to determine the effectiveness of the SPI for adults experiencing suicide-related distress. Systematic searches of international, peer-reviewed literature were conducted in six databases (Cochrane Trials, Embase, Emcare, Medline, PsycINFO and Web of Science), including terms for safety planning, suicide, and suicide-related outcomes. A total of 565 results were included for screening. Result screening (title/abstract and full-text), data extraction and critical appraisal were conducted in duplicate. Twenty-six studies met the inclusion criteria. Studies were primarily quantitative ( n  = 20), largely with general adult or veteran samples; a small number of studies explored the perspectives of staff and significant others. Half of the studies included the SPI as a standalone intervention, while the other half examined the SPI in combination with other interventions. Most interventions were delivered in-person, with a hard-copy safety plan created, while a smaller number explored internet-based interventions. Primary measures included: suicidality (ideation, behavior, deaths; 10 studies), suicide-related outcomes (depression, hopelessness; 5 studies) and treatment outcomes (hospitalizations, treatment engagement; 7 studies). The evidence supports improvements in each of these domains, with complementary findings from the remaining quantitative and qualitative studies suggesting that the SPI is a feasible and acceptable intervention. While positive, these findings are limited by the heterogeneity of interventions and study designs, making the specific impact of the SPI difficult to both determine and generalize. Conversely, this also points to the flexibility of the SPI. Highlights: The Safety Planning Intervention (SPI) is a valuable indicated intervention for general adult and veteran populations experiencing suicide-related distress, primarily in face-to-face, clinical settings. Quantitative findings indicate associations between the SPI and improvements in suicidal ideation and behavior, decreases in depression and hopelessness, along with reductions in hospitalizations and improvements in treatment attendance. Qualitative studies suggest the SPI is acceptable and feasible, with areas for development. SPIs have been shown to be adaptable to the clinical area in its modality (digital or paper-based), delivery (face-to-face or online), facilitation (clinician or self-administered) and multiplicity (as stand-alone or combined intervention).